High-dose-rate Brachytherapy Monotherapy in Patients With Localised Prostate Cancer: Dose Modelling and Optimisation Using Computer Algorithms. - Dabic-Stankovic, K.; Rajkovic, K.; Stankovic, J.; Marosevic, G.; Kolarevic, G.; Pavicar, B. (Clinical Oncology, 2024)
Interstitial high-dose-rate brachytherapy (HDR-BT) is an effective therapy modality for patients with localized prostate carcinoma. The objectives of the study were to optimise the therapy regime variables using two models: response surface methodology (RSM) and artificial neural network (ANN). Thirty-one studies with 5651 patients were included (2078 patients presented as low-risk, 3077 patients with intermediate-risk, and 496 patients with high-risk). A comparison of these therapy schedules was carried out using an effective biologically effective dose (BED ef) that was calculated assuming the number of treatment days and dose (D) per day. The modelling and optimization of therapy parameters (BED ef and risk level) in order to obtain the maximum biochemical free survival (BFS) were carried out by the RSM and ANN models. An optimal treatment schedule (BFS = 97%) for patients presented with low-risk biochemical recurrence would be D = 26 Gy applied in one application, 2 fractions at least 6 h apart, within an overall treatment time of 1 day (BED ef = 251 Gy) by the RSM and ANN model. For patients presented with intermediate- or high-risk an optimal treatment regime (BFS = 94% and 90%, respectively) would be D = 38 Gy applied in one application, 4 fractions at least 6 h apart, with an overall treatment time of 2 days (BED ef = 279 Gy) by the RSM and ANN models. The RSM and ANN models determine almost the same optimal values for the set of predicted therapy parameters that make a feasible selection of an optimal treatment regime. • HDR-BT is an effective therapy modality for patients with localised prostate carcinoma. • Optimisation of HDR-BT regime variables was carried out by the RSM and ANN models. • The RSM and ANN models determined almost the same optimal values.